Kampoeng Djadhoel, Laboratorium Hidup : Eksplorasi Ekologi dan Etika Wisata - Dyan Triana Putra; Septa Intiar (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the implementation of the living laboratory concept in the management of Kampoeng Djadhoel as a sustainable tourism destination. The research background is based on the need to integrate ecological aspects, environmental ethics, and community empowerment into tourism practices that provide educational experiences while preserving the local environment and culture. The method used is a qualitative case study involving in-depth interviews, participatory observations, focus group discussions, and document analysis over six months. The research informants include destination managers, local communities, tourists, and local government. The main findings reveal that Kampoeng Djadhoel has unique characteristics as a living laboratory with an adaptive-collaborative management model, strong environmental ethics practices, and significant impacts on tourists’ ecological awareness and local community welfare. The study also uncovers cognitive transformation among visitors and improved economic benefit distribution supporting destination sustainability. The implications of this research contribute theoretically to the development of an integrated sustainable tourism model and practically to the management of urban tourism destinations that prioritize community collaboration and environmental conservation.